Star Fruit Intoxication (Anwer Khan Modern Medical College Journal, 2017)
Now a day Acute Kidney Injury and Chronic Kidney Disease are the two common problems worldwide with increased mortality and morbidity as well as health care cost. Nephrotoxicity and neurotoxicity by the Star fruit, sometimes fatal, is far more frequent than reported. Star fruit belongs to the Oxalidaceae family, species Averrhoea carambola, is a popular fruit among Orientals. The aim of the study is to create awareness among the population regarding star fruit intoxication, to reduce the development of Acute Kidney Injury in general population, to reduce the mortality and burden of morbidity from chronic renal failure, to reduce the mortality of the patients of End stage renal disease taking regular haemodialysis and to reduce the mortality and burden of morbidity of the people suffering from Diabetes mellitus and Hypertension. Star fruit juice produces acute renal injury not only through the obstructive effect of calcium oxalate crystals, but also inducing apoptosis of renal epithelial cells, which may be caused by the levels of oxalate in the fruit. There have been reports of hiccup, confusion and occasional fatal outcomes in uremic patients after ingestion of star fruit. An excitatory neurotoxin from star fruit has been implicated although the exact nature of this toxic substance has not been identified. High quantities of oxalate in empty stomach and dehydrated state may pose an additional risk for development of renal injury. To avoid acute oxalate nephropathy, pure sour carambola juice or mild diluted post pickled juice should not be consumed in large amounts, especially in an empty stomach and dehydrated state. It is recommended that uremic patients should totally abstain from star fruit due the rare but potentially fatal complications.Anwer Khan Modern Medical College Journal Vol. 6, No. 2: July 2015, P 30-33